Control integrado de "escoba de bruja" (Crinipellis perniciosa) y moniliasis (Moniliophthora roreri) del cacao en Urabá. (1989)
The strategy of integrated management of witches'broom and monilia pod rot disease contemplates the employ of two control systems: phytosanitary pruning and systemic fungicides. Since 1983, at the ICA Tulenapa Research Center, located in the Urabá region, was evaluated the technical and economics efficiency of the phytosanitary pruning alone and associate to the aplication of the Triadimefon (1.5 I/ha), Pyracarbolid (2.5 I/ha) and Oxicarboxin (1.5 I/ha) for the control of these diseases. The products were applied during the second semester of each year. The results demostrate that all treatments reduced significantly the incidence of diseases yet to do not exist differences between phytosanitary pruning more fungicides, and phytosanitary pruning alone. In average for all treatments, the percentages of infection by monilia pod rot decreased from 71% to 14 1 7o. At the same time, the broom index passed from 163 to 47 since 1983 to 1986. In all treatments the yield increased significantly, compared with the 1982-1983 period of the same experimental area (250 kg/ha), and with respect to the average of all region, which was 400 kg/ha during 1986. The tminimal production obtained throughout of this experiment was 900 kg/ha. The eco nomical and technical analysis of treatments permit to conclude that the fungicide application is not a recomendabie alternative at level of commercial crops. However, should be continue its study and evaluation with the purpose to define a better system of application, and by this way to improve their expression of control which was found at preliminary works. At level of traditional crops their application would result uneconomic, compared with the phytosanitary pruning actually recommended So, the general conclusion is that the unique efficient and economic alternative for the control of these diseases is the phytosanitary pruning.